Mechanical degradation of TiO(2) nanotubes with and without nanoparticulate silver coating - Shivaram, Anish (J Mech Behav Biomed Mater, 2016)
The primary objective of this research was to evaluate the extent of mechanical degradation on TiO(2) nanotubes on Ti with and without nano-particulate silver coating using two different lengths of TiO(2) nanotubes- 300nm and ~ 1µm, which were fabricated on commercially pure Titanium (cp-Ti) rods using anodization method using two different electrolytic mediums - (1) deionized (DI) water with 1% HF, and (2) ethylene glycol with 1% HF, 0.5 wt%. NH(4)F and 10% DI water. Nanotubes fabricated rods were implanted into equine cadaver bone to evaluate mechanical damage at the surface. Silver was electrochemically deposited on these nanotubes and using a release study, silver ion concentrations were measured before and after implantation, followed by surface characterization using a Field Emission Scanning Electron Microscope (FESEM). In vitro cell-material interaction study was performed using human fetal osteoblast cells (hFOB) to understand the effect of silver coating using an MTT assay for proliferation and to determine any cytotoxic effect on the cells and to study its biocompatibility. No significant damage due to implantation was observed for nanotubes up to ~1 µm length under current experimental conditions. Cell-materials interaction showed no cytotoxic effects on the cells due to silver coating and anodization of samples.